Optimization of Processing Conditions for the Production of Clarified Banana (Musa Sapientum) Juice Drink and Its Storage Stability - Lee, Wai Cheng (2006)
This study was carried out on the optimization of hot water extraction and enzymatic treatment for producing clarified banana juice. A response surface methodology (RSM) was used to determine the optimum extraction temperature and time to produce banana juice extract. Banana juice was extracted using hot water at different extraction temperatures (35-95ºC) and time (30-120 min). The effects of these extraction conditions on juice yield, total soluble solids (ºBrix), banana odour and taste were studied by employing a second-order central composite design. The coefficient of determination, R2, for juice yield, total soluble solids (ºBrix), banana odour and taste were greater than 0.900. Analysis of the regression coefficients showed that temperature was the most important factor that affected the characteristics of the banana juice extract as it exerted a highly significant influence (p<0.001) on all the dependent variables. An increase in temperature and extraction time of hot water extraction resulted in an increase in juice yield, total soluble solids, banana odour and taste of the banana juice extract. Based on response surface and contour plots, the optimum conditions obtained for hot water extraction of banana juice were 95ºC for 120 minutes. This optimum condition gave maximum juice yield (39.55 %), total soluble solids (9.19 °Brix), banana odour (6.91 scores) and taste (5.87 scores). Optimization of enzymatic treatment of the banana juice extract was then carried out using pectinase (Pectinex Ultra SP-L) at various enzyme concentrations (0.01–0.1%), temperatures (30–50ºC) and times (30–120 min). The effect of these enzyme treatments on filterability, clarity, turbidity and viscosity of the juice were studied by employing a second order central composite design. The coefficient of determination, R2 values for filterability, clarity, turbidity and viscosity were greater than 0.900. Statistical analysis showed that filterability, clarity, viscosity and turbidity were significantly (p<0.05) correlated to enzyme concentration, incubation temperature and incubation time. Enzyme concentration was the most important factor affecting the characteristics of the banana juice as it exerted a highly significant influence (p<0.01) on all the dependent variables. An increase in time and/or concentration of enzyme treatment was associated with an increase in filterability and clarity, and decrease in turbidity and viscosity. Based on response surface and contour plots, the optimum conditions for clarifying banana juice obtained were: 0.084% enzyme concentration, incubation temperature of 43.2ºC and incubation time of 80 min. The response functions were calculated from the final polynomial, and the response were filterability (0.073 second -1), clarity (0.006 Abs), turbidity (0.92 NTU) and viscosity (1.89 cps). The storage stability of clarified banana juice was evaluated for 24 weeks using bentonite and a combination of gelatin and bentonite as fining agents and stored at 4, 25 and 37ºC. The results indicated that fining agents, storage temperature and storage time had a significant (p<0.001) effect on turbidity, clarity, total polyphenol, protein content and browning index, colour (L, a and b values), pH, titratable acidity (TA), total soluble solids (TSS) of clarified banana juice. It was observed that both bentonite and combination of gelatin and bentonite treatments produced juice of better quality than control. These treatments were effective in reducing turbidity, total polyphenol, protein content and browning while improving clarity and lightness of the clarified banana juice. Bentonite treated juice was the least turbid and its organoleptic quality did not change significantly throughout storage. The temperature used for storage of juice had a marked effect on the rate and amount of haze formed during storage. Bentonite treated juice stored at 4ºC was found to be the most suitable storage combination with the lowest rate of increase in turbidity and colour change as well as lowest rate of decrease in clarity, total polyphenol and protein content during storage.